2009
DOI: 10.1177/0040517508099387
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Pressure of Knitted Fabrics Estimated in Relation to Tensile Load Under Extension and Recovery Processes by Simultaneous Measurements

Abstract: Clothing pressure of knitted fabrics was estimated by two methods using an air pack. In Case 1, the pressure by shrinkage of extended fabrics was measured by an air pack put on the cylinder, in which the air pack was inserted between the knitted fabric extended to a desired strain and the cylinder as a basic substance. The tensile load at a given strain of the knitted fabric covered on the cylinder was estimated from the same strain of the extended knitted fabric measured by a strip biaxial tensile tester. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Since clothing pressure largely depended on its biaxial extension and stress relaxation properties [81], research studies have been conducted to find the relationship between the clothing pressure of knitted fabrics and stress under extension and recovery processes [82,83]. The pressure behavior of tubular knitted elastic fabrics at different extension levels during 48 hours was investigated and it was found that the stitch length and extension rate are the vital factors that affects the interfacial pressure and pressure reduction [84].…”
Section: Fabric Construction and Mechanical Propertiesmentioning
confidence: 99%
“…Since clothing pressure largely depended on its biaxial extension and stress relaxation properties [81], research studies have been conducted to find the relationship between the clothing pressure of knitted fabrics and stress under extension and recovery processes [82,83]. The pressure behavior of tubular knitted elastic fabrics at different extension levels during 48 hours was investigated and it was found that the stitch length and extension rate are the vital factors that affects the interfacial pressure and pressure reduction [84].…”
Section: Fabric Construction and Mechanical Propertiesmentioning
confidence: 99%
“…The relationship between the voltage and pressure is obtained through the measured data, and the relation coefficient is inputted into the system to obtain the required clothing pressure. [17][18][19][20]…”
Section: Application Study Of Ultra-low-modulus Knitted Fabricmentioning
confidence: 99%
“…์˜๋ณต์˜ ์ฐฉ์šฉ์œผ๋กœ ์ธํ•ด ์ธ์ฒด๊ฐ€ ๋Š๋ผ๋Š” ์˜๋ณต์••(clothing pressure)์€ ์˜๋ณต์˜ ๊ตฌ์†์„ฑ๊ณผ ์šด๋™๊ธฐ๋Šฅ์„ฑ์„ ๊ฒฐ์ •ํ•˜๋Š” ์ค‘์š” ํ•œ ์š”์ธ์ด ๋  ๋ฟ๋งŒ ์•„๋‹ˆ๋ผ ์˜๋ณต์˜ ์ฐฉ์šฉ ์พŒ์ ์„ฑ๋Šฅ๊ณผ๋„ ๋ฐ€์ ‘ ํ•œ ๊ด€๊ณ„๊ฐ€ ์žˆ๋‹ค [1]. ์ ์ ˆํ•œ ์˜๋ณต์••์€ ์‹ ์ฒด ์ผ๋ถ€์˜ ๋ถˆํ•„์š”ํ•œ ๋™์ž‘์„ ๋ง‰์•„ ์šด๋™์„ฑ์„ ์ตœ๋Œ€ํ™”์‹œ์ผœ ์ฃผ๋ฉฐ, ๊ทผ์œก์„ ๊ฐ์‹ธ ๋ฐ›์ณ ์คŒ์œผ๋กœ์จ ์‹ ์ฒด๋ฅผ ๋ณดํ˜ธํ•˜๋Š” ์—ญํ• ์„ ํ•  ๋ฟ๋งŒ ์•„๋‹ˆ๋ผ [2], ์™ธ๊ณผ ์ˆ˜์ˆ ํ™˜์ž๋‚˜ ํ™”์ƒํ™˜์ž์˜ ์ƒ์ฒ˜๋ถ€์œ„์— ์ ์ ˆํ•œ ์••๋ฐ•์„ ๊ฐ€ํ•จ์œผ ๋กœ ํ•ด์„œ ์ƒ์ฒ˜๋ถ€์œ„๋ฅผ ๋ถ€๋“œ๋Ÿฝ๊ฒŒ ํ•˜๋ฉฐ ํ”ผ๋ถ€์กฐ์ง ์žฌ์ƒ์— ๋„์›€ ์„ ์ค„ ์ˆ˜ ์žˆ๋‹ค [3].…”
Section: ์„œ ๋ก unclassified